HEALTHCARE RESOURCES UTILIZATION AND TEMPORARY DISABILITY IN POPULATION AGED 50-64 ACCORDING TO THE EPIDEMIOLOGICAL ESSE-RF STUDY - A. V. Kontsevaya; Yu. A. Balanova; A. E. Imaeva; A. D. Deev; A. V. Kapustina; G. A. Muromtseva; S. E. Evstifeeva; S. A. Shalnova (Столичная издательская компания, 2017)
Aim. To analyze health care resource utilization and temporary disability in people of pre-retirement age in the Russian population.Material and methods. The analysis was carried out on the basis of the ESSE-RF study materials (13 regions of the RF). Standard epidemiological survey methods and evaluation criteria were used. The analysis included results of a survey of the ESSE-RF study participants about health care resource utilization and temporary disability (TD) during 12 months before the survey. The following characteristics were ascertained: a number and reasons of outpatient visits for medical assistance, hospital admissions (including duration of in-hospital treatment), emergency calls and temporary disability (a number of days and cases), their mean number per one study participant, mean number of cases and days of TD per 100 working participants, associations with social-demographic parameters, risk factors, chronic non-communicable diseases, stress and anxiety levels by the Hospital Anxiety and Depression Scale (HADS).Results. A total of 8334 people aged 50-64 years were examined: men - 2784 (33%) and women - 5550 (67%). A share of the hospitalized (at least one time) was 11% in the age group of 50-54 years, 12% - in the age group of 55-59 years and by the age of 60-64 this indicator increased to 15%. 20% of the participants at least one time were admitted to hospital and/or called an ambulance. A share of people who had utilized health care resources at least one time was increasing with age. Unemployed people were hospitalized more frequently than employed ones. Number of chronic non-communicable diseases correlated with the probability of hospitalization and/or emergency call. Categories 2 and 3 of disability, presence of diabetes mellitus, ischemic heart disease and hypertension were statistically significantly associated with the probability of hospitalization and/or emergency call. Smoking did not increase the probability of hospitalization and/or emergency call in comparison with absence of this risk factor, at that, people who had given up smoking were 1.3 times more likely to be hospitalized than non-smokers. People with low and moderate alcohol consumption were hospitalized and called an ambulance significantly less often than those who abstained from alcohol. Clinically significant anxiety increased the probability of hospital admission and/or emergency call as compared to people without this factor by the HADS. Subclinical and clinically significant anxiety, mean and high levels of stress were associated with the probability of hospitalization and/or emergency call. Number of TD days turned out to be rather low - 0.3 day per 1 working man and 0.4 day - per 1 working woman, this index did not significantly differ with age.Conclusion. So, pre-retirement age (50-64 years) is characterized by increase in health care resource utilization due to health state worsening. At the same time significant share of people of this age (40%) did not seek medical help. These 40% of pre-retirement age people can be possible reserve for health state improvement by means of their active involvement in preventive activity of primary health care system (the study had been conducted before the preventive medical examination program starting).